PENGARUH STRUKTUR KEPEMILIKAN TERHADAP FINANCIAL CONSTRAINTS - Irny Astuti Amalia; Fuad Fuad (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of ownership structure on the financial constraints of non-financial companies listed on the Kompas 100 Index in 2012-2021. This study uses financial constraints with the calculation of the KZ index as the dependent variable, and managerial ownership, institutional ownership, foreign ownership, blockholder ownership, concentrated ownership as independent variables, as well as leverage, ROA, current ratio, size, dividend payout, Tobin’s Q as variables control.The population of this study is non-financial companies listed on the Kompas 100 Index for 2012-2021 using a purposive sampling method, resulting in 541 research samples using an unbalanced panel data model. Generalized Least Squares (GLS) are used to test the hypothesis of this study.The findings from this study prove that blockholder ownership variables are found to be significantly negatively related to financial constraints; managerial ownership, institutional ownership, foreign ownership, and concentrated ownership are not significant to financial constraints through the KZ proxy. While the research findings with the SA index as a proxy, the concentrated ownership variable was found to be significantly negatively related to financial constraints; managerial ownership, institutional ownership, foreign ownership, and blockholder ownership are not significant to financial constraints.